Efektivitas Implementasi Model Pembelajaran ICARE Terhadap Hasil Belajar Kimia Siswa Pada Materi Asam Basa Di SMA Budi Luhur Kembang Mertha - Dewa Ayu Agung Raka Sri Adnyani; Desire Rumondor; I Dewe Ketut Anom (Chemistry Department, Universitas Negeri Manado, 2023)
The purpose of this study was to determine the Effectiveness of the Implementation of the ICARE Learning Model on Student Chemistry Learning Outcomes in Acid-Base Material. This research was conducted in class XI MIA SMA Budi Luhur Kembang Mertha in the 2022/2023 academic year. A total of 24 students of class XI MIA were selected as the research sample. This research is a quantitative study using an experimental method with a one-group pretest-posttest design. The data collection technique uses a learning achievement test which is given a pretest before the learning process is carried out and a posttest after the learning process is carried out. From these results it can be concluded that the implementation of the ICARE learning model can effectively improve students' chemistry learning outcomes in the subject matter of class XI acids and bases at SMA Budi Luhur Kembang Mertha.